Kontribusi Produk Pembiayaan Amanah Dalam Meningkatkan Nasabah PT Pegadaian (Persero) UPS Tukmudal Kabupaten Cirebon - Sunardi Edirianto; Alvin Alvin; Paturohman Paturohman; Vera Herawati (Ecobankers : Journal of Economy and Banking, 2021)
This research is about how the system of trust financing products at PT. Pegadaian (Persero) UPS Tukmudal Cirebon Regency and the efforts made by PT. Pegadaian (Persero) UPS Tukmudal Cirebon Regency in increasing customers. This study aims to obtain data on Amanah financing products and efforts to increase customers of PT. Pegadaian (Persero) UPS Tukmudal Cirebon Regency. This study uses a descriptive qualitative methodology. This research is in the form of a field that is directly involved in the field to dig up data. Data was collected by means of interviews, namely to employees of PT. Pegadaian (Persero) UPS Tukmudal Cirebon Regency and several Amanah financing customers. The results of the study stated that the Amanah financing product was in accordance with the Umbrella Fatwa. 92/DSN-MUI/IV/20014 concerning the financing of the Amanah accompanied by Rahn (al-Tanwil al-Mauthuq bi al-Rahn). This trust financing uses indicators in analyzing prospective customers, namely character, capacity, collateral, capital, condition of economy, and constraints. Based on the results of the study, it can be concluded that the financing of Amanah products and the analysis in it have a major impact on the ongoing process of financing. The impact is in preventing the occurrence of bad financing, as well as in improving services to customers, either directly or indirectly. So that there is a need for a more complete analysis such as capital, conditions of economy, and constraints in analyzing prospective customers to improve financing in Amanah products at PT. Pegadaian (Persero) UPS Tukmudal Cirebon Regency Abstrak Penelitian ini mengenai bagaimana sistem produk pembiayaan amanah di PT. Pegadaian (Persero) UPS Tukmudal Kabupaten Cirebon dan upaya yang dilakukan PT. Pegadaian (Persero) UPS Tukmudal Kabupaten Cirebon dalam meningkatkan nasabah. Penelitian ini bertujuan untuk memperoleh data tentang produk pembiayaan Amanah dan upaya untuk meningkatkan nasabah PT. Pegadaian (Persero) UPS Tukmudal Kabupaten Cirebon. Penelitian ini menggunakan metodologi kualitatif deskriptif. Penelitian ini dalam bentuk lapangan yaitu terjun langsung kelapangan untuk menggali data. Pengumpulan data dilakukan dengan cara wawancara yaitu kepada karyawan PT. Pegadaian (Persero) UPS Tukmudal Kabupaten Cirebon dan beberapa nasabah pembiayaan Amanah. Hasil penelitian menyatakan bahwa produk pembiayaan Amanah sesuai dengan Fatwa Payung hukum dari gadai syariah berpegang pada Fatwa DSN MUI No. 92/DSN-MUI/IV/20014 tentang pembiayaan Amanah yang disertai Rahn (al-Tanwil al-Mauthuq bi al-Rahn). Pembiayaan amanah ini menggunakan indikator dalam menganalisis calon nasabah yaitu character, capacity, collateral, capital, condition of economy, dan constraint. Berdasarkan hasil penelitian dapat disimpulkan bahwa pembiayaan pada produk Amanah serta analisis di dalamnya mempunyai dampak yang besar dalam proses berlangsungnya pembiayaan. Dampaknya ialah dalam mencegah terjadinya pembiayaan yang buruk, juga dalam meningkatkan pelayanan kepada nasabah, baik secara langsung maupun tidak langsung. Sehingga perlu adanya analisis yang lebih lengkap seperti capital, condition of economy, dan constraint dalam menganalisis calon nasabah untuk penyempurnaan pembiayaan dalam produk Amanah pada PT. Pegadaian (Persero) UPS Tukmudal Kabupaten Cirebon